THE EFFECT DISCOVERY LEARNING MODEL STUDENTS SCIENCE LITERACY IN INDONESIA - Haryono; Nofirman; Ellina Rienovita; Mohammad Edy Nurtamam; Yuyun Suprapto; Andi Rahman; Andri Kurniawan; Tomi Apra Santosa (International Journal of Teaching and Learning, 2023)
This study aims to determine the effect of discovery learning model on students' science literacy in Indonesia. This research is a type of meta-analysis research. Data sources came from 10 national and international journals published in 2020-2023. Data search techniques in this study through Google Scholar, ERIC, DOAJ and ProQuest. The data analysis technique calculates the effect size value with the help of the JSAP application. The results of this study concluded that the average effect size value was 0.825 with large criteria. This finding explains that the discovery learning model has a positive effect on students' science literacy. This research provides important information about the application of the discovery learning model in learning